Determination of growth, mass, and body mass index of harbour porpoises (Phocoena phocoena): implications for conservational status assessment of populations - Stepien, Emilie Nicoline; Nabe-Nielsen, Jacob; Hansen, Kirstin Anderson; Kristensen, Jakob Højer; Blanchet, Marie-Anne; Brando, Sabrina; Desportes, Geneviève; Lockyer, Christina; Marcenaro, Lauro; Bunskoek, Paulien; Kemper, José; Siebert, Ursula; et al. (Global Ecology and Conservation, 2023)
Longitudinal data on individual growth and seasonal changes in body mass, girth, and blubber thickness are rarely available for cetaceans, making it difficult to assess their population composition and individual nutritional condition. During different time intervals from 1997 to 2020, we collected longitudinal data on length, body mass, girth,and blubber thickness from seventeen harbour porpoises (Phocoena phocoena) in human care. We compared Gompertz and von Bertalanffy growth curves to collected length data at age 0–4 years for five individuals with known dates of birth. Von Bertalanffy had the lowest AICc value and was used to predict the birth year of twelve animals which age had previously been estimated based on tooth ring analysis and ossification of flipper bones. The growth curve was accurate within 1 yr. of age estimates. Within the first year, the calves grew 66%, attaining 84% of their adult length, and reached asymptotic length at age 3–4. For adults, there were large seasonal variations in body mass, body mass index, girth, and blubber thickness, with up to 28% of variation in body mass between seasons. We predicted individual body mass within ± 2 kg using measurements of length and girth, allowing estimation of body mass index of individuals with unknown mass. Our findings enable monitoring and assessments of population composition as well as nutritional condition of individual harbour porpoises, which is crucial for assessing conservational status and guiding management.